Classroom Interactions as Representations of Multiculturalism: A Critical Discourse Analysis - Tampubolon, Muhammad Ahsan; Sukmawati, Nur Najibah; Nasution, Sukma Septian (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2024)
In countries with multicultural societies, representatives of different cultures are found interacting in a community such as the workplace, neighborhood or school. Of various origins, races, religions, tribes, even nations, they practice interpersonal and transactional communication every day. Therefore, it is important for all members of each community to have a multicultural understanding of differences. Educational institutions are agents responsible for instilling the values ​​of multiculturalism through education. Multiculturalism as an ideology has become a worldwide discussion at the end of the century due to the large number of migrants around the world making the avoidance of local residents and newcomers from cultural conflict a major issue. Therefore, it is important to simultaneously carry out functional intercultural relations for an effective educational process to create multicultural understanding. To do this, teachers need to have social and cultural competence by integrating ethnic and cultural literacy in teaching practices to end racism, sexism, prejudice and other types of discrimination that have the potential to occur in classes consisting of diverse cultural backgrounds.